2017
DOI: 10.1038/s41598-017-07412-4
|View full text |Cite
|
Sign up to set email alerts
|

Routes Obey Hierarchy in Complex Networks

Abstract: The last two decades of network science have discovered stunning similarities in the topological characteristics of real life networks (many biological, social, transportation and organizational networks) on a strong empirical basis. However our knowledge about the operational paths used in these networks is very limited, which prohibits the proper understanding of the principles of their functioning. Today, the most widely adopted hypothesis about the structure of the operational paths is the shortest path as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Gao et al showed that the paths of packets going through the internet are also detoured in a non-negligible extent 30 and they show that the hierarchical policies of internet packet routing may be responsible for the major proportion of the inflation. Detours have been identified in road networks by Zhu et al 31 and in cattle pen systems by Grandin 32 , while similar phenomena was reported in airport 10,27 and brain networks 10,33 too.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Gao et al showed that the paths of packets going through the internet are also detoured in a non-negligible extent 30 and they show that the hierarchical policies of internet packet routing may be responsible for the major proportion of the inflation. Detours have been identified in road networks by Zhu et al 31 and in cattle pen systems by Grandin 32 , while similar phenomena was reported in airport 10,27 and brain networks 10,33 too.…”
Section: Introductionmentioning
confidence: 55%
“…traveling between locations in a city using public transportation). The available navigational datasets [1][2][3][4] and models [3][4][5][6][7][8][9][10] considering networked systems, mostly target to uncover the average properties of a group of subjects and capture collective human behavior. Thus existing datasets do not have sufficient data or appropriate tracing methods permitting the analysis of long-term individual patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al showed that the paths of packets going through the internet are also detoured to a non-negligible extent 21 , and they showed that the hierarchical policies of internet packet routing may be responsible for a major proportion of the inflation. Detours have been identified in road networks by Zhu et al 22 and in cattle pen systems by Grandin 23 , while similar phenomena were also reported in airports 10,24 and brain networks 10,25 .…”
mentioning
confidence: 53%
“…As a result, real paths will be somewhat longer than the shortest alternatives, but the detours will be characteristic to the individual taking them, as no two individuals may abstract the same hierarchy of the network. Although there are existing models assuming latent hierarchical scaffolds aiding navigation 6,10,[17][18][19][20] , this is the first study processing sufficient individual human navigation data to visualize and analyse these individually created hierarchies.…”
mentioning
confidence: 99%